The influence of collusion on price changes: New evidence from major cartel cases - Korbinian von Blanckenburg; Alexander Geist; Konstantin Arkadievich Kholodilin (Verein für Socialpolitik, 2010)
In this paper, we compare the distribution of price changes between collusive and non-collusive periods for ten major cartels. The first moments focus on previous research. We extend the discussion to the third (skewness) and fourth (kurtosis) moments. However, none of the above descriptive statistics can be considered as a robust test allowing a differentiation between competition and cartel. Therefore, we implement the Kolmogorov-Smirnov test. According to our results, 8 out of 10 cartels were successful in controlling the market price for a number of years. The proposed methodology may be used for antitrust screening and regulatory purposes.
Keywords: L10; L60; L40; 330; cartel detection; collusion; competition policy